EVALUASI KEMAMPUAN MEMBACA SISWA SEBELUM DAN SESUDAH MENGGUNAKAN FLASHCARD DAN CARDMATCH - M Ikhwanul Hakim (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2020)
The research objective is to determine the reading ability of students before and after using Flashcards and Cardmatch Media. The research method in this research is a qualitative descriptive approach. The reading ability of students before the application of the flashcard and cardmatch methods was <60 with the highest score of 58.33, while the reading ability of students after the application of the flashcard method was > 77 with the highest score of 85.33, the reading ability of students after applying cardmatch method wa s> 77 with the highest score 85.33. Meaning that the students' reading ability was better after using flashcard and cardmatch methods, while the higher comparison between flashcard and cardmatch methods was flashcards, with the number of students who had the highest score of 85.33 with a percentage of 68%, 17 students were greater than cardmatch which has the highest score of 85.33 with a percentage of 28% of 7 students of 25 students